Mucoepidermoid Carcinoma of Uterine Cervix: A Distinct Pathological and Clinical Entity - Ilker Selcuk; Bulent Ozdal; Mengu Turker; Alp Usubutun; Tayfun Gungor; Mehmet Mutlu Meydanli (Hindawi Limited, 2015)
Mucoepidermoid carcinoma of uterine cervix is a rare tumor that has some individual features. Defining risk factors after surgery shape the postoperative treatment modality on cervical cancer patients. Although there is not a well-known strategy for the postoperative follow-up of mucoepidermoid carcinoma, the aggressive behaviour of this tumor makes the gynecological oncologists choose liberal therapies on these patients.